Cinderella - Rossini, Gioacchino 1792-1868; Montresor, Beni (Alfred A. Knoft, 1965)
Recounts Rossini's operatic version of the tale of the mistreated cinder maid who stepped into a glass slipper and the arms of her Prince Charming.